2019
DOI: 10.1002/bbb.2056
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the valorization of poultry litter via thermochemical processing

Abstract: Waste management via thermochemical processing is gaining increasing importance as larger volumes of solid waste are generated yearly. The poultry industry generates a variety of wastes, of which the largest stream in terms of volume is the litter. In this study, three thermodynamic models were developed on ASPEN Plus v8.8 for pyrolysis, in‐line steam reforming, and gasification of poultry litter. At optimal pyrolysis of 450 °C, the product yield was 43.74 wt% bio‐oil, 6.71 wt% gas, and 49.55 wt% char. The opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
4
6
0
Order By: Relevance
“…It can be observed that for all three residues, the selectivity of hydrogen and carbon monoxide increases with temperature while carbon dioxide and methane drops with temperature. This has also been observed for the gasi cation of poultry litter [24] and switchgrass [25]. The optimum temperature for hydrogen selectivity for pseudo-stem and peels is 900 o C while that of leaves is 700 o C. At these optimum conditions, the hydrogen molar selectivity in the product stream is 56%, 55% and 53% for pseudo-stem, peels and leaves respectively.…”
Section: Effect On Temperature On Product Selectivitysupporting
confidence: 55%
See 1 more Smart Citation
“…It can be observed that for all three residues, the selectivity of hydrogen and carbon monoxide increases with temperature while carbon dioxide and methane drops with temperature. This has also been observed for the gasi cation of poultry litter [24] and switchgrass [25]. The optimum temperature for hydrogen selectivity for pseudo-stem and peels is 900 o C while that of leaves is 700 o C. At these optimum conditions, the hydrogen molar selectivity in the product stream is 56%, 55% and 53% for pseudo-stem, peels and leaves respectively.…”
Section: Effect On Temperature On Product Selectivitysupporting
confidence: 55%
“…What was quite conspicuous for all three residues in the drop in methane and rise in CO 2 content with increasing AFR. This has also been observed for the gasi cation of poultry litter [24] and switchgrass [25]. The greater availability of oxygen (from air) at higher temperatures ensure a more intense gasi cation of the carbon load leading to higher oxygenated products and lesser methane.…”
Section: Effect Of Air-fuel Ratio (Afr) On Product Selectivitymentioning
confidence: 62%
“…4 For mitigation purposes, thermochemical processing of biomass has received significant attention because it doubles as a technology for clean energy generation as well as for the production of renewable energy chemicals (biofuels). 5,6 Oil palm (Elaeis guineensis) is grown in semi-wild groves in tropical countries. In the production of palm oil, large quantities of biomass wastes (such as trunks, fronds, fibers, shells, and empty fruit bunches) are generated.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, agricultural waste is a major type of municipal solid waste that has been increasingly creating environmental hazards in communities due to their inefficient and improper disposal 4 . For mitigation purposes, thermochemical processing of biomass has received significant attention because it doubles as a technology for clean energy generation as well as for the production of renewable energy chemicals (biofuels) 5, 6 …”
Section: Introductionmentioning
confidence: 99%
“…The non-conventional components are modelled by their proximate and ultimate analyses. The Peng-Robinson with Boston-Mathias function (PR-BM) property method was considered for this simulation as it provides good accuracy for gasification simulations [6,9,10]. The supercritical water gasification process is simulated using the RYield and RGibbs block as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%